A Study on Financial Statement Analysis through Comparative and Common Size Analysis of Bharat Electronics Limited (BEL) - Prudhvi Raj , K; Thanuja, S. (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This study explores the financial performance of Bharat Electronics Limited (BEL), a leading Indian public sector undertaking specializing in defence and non-defence electronics. Utilizing comparative and common size analysis, the research assesses BEL’s profitability, liquidity, solvency, and overall financial health. The study relies on qualitative insights derived from BEL’s operational strategies and sectoral contributions. Findings highlight strategic diversification and a commitment to innovation. Recommendations focus on enhancing R&D, optimizing the supply chain, and strengthening strategic partnerships.